Cerebrospinal fluid α synuclein concentrations in patients with positive AD biomarkers and extrapyramidal symptoms - Winkel, Izabela; Ermann, Natalia; Żelwetro, Agnieszka; Sambor, Bożydar; Mroczko, Barbara; Kornhuber, Johannes; Paradowski, Bogusław; Lewczuk, Piotr (Journal of Neural Transmission, 2021)
Extrapyramidal symptoms (EP) are not uncommon in Alzheimer’s Disease (AD); when present, they negatively influence the course of the disorder. A large proportion of AD patients shows concomitant Lewy bodies’ pathology post mortem. Total α Synuclein (αSyn) concentrations are frequently increased in the cerebrospinal fluid (CSF) of AD patients, but are decreased in Parkinson’s Disease (PD) and Dementia with Lewy Bodies (DLB). αSyn CSF concentrations in AD patients with EP (EP+) have not been reported so far. αSyn and the four Neurochemical Dementia Diagnostics (NDD) CSF biomarkers, (Aβ1-42, Aβ42/40, Tau, and pTau181), interpreted according to the Erlangen Score algorithm, were measured in patients with positive NDD results and presence of extrapyramidal symptoms (NDD + / EP+; n = 26), in patients with positive NDD results and absence of extrapyramidal symptoms (NDD+ / EP−; n = 54), and in subjects with negative NDD results (NDD−; n = 34). Compared to the NDD− controls (379.8 ± 125.2 pg/mL), NDD+ patients showed, on average, highly significantly increased CSF αSyn (519 ± 141.3 pg/mL, p < 0.01), but without differences between NDD+ / EP+ and NDD+ / EP− subgroups ( p = 0. 38). Moderate but highly significant association was observed between concentrations of αSyn and Tau (r = 0.47, p < 0.01) and pTau181 (r = 0.65, p < 0.01). Adjusted for diagnoses, age, and sex, subjects with more advanced neurodegeneration on neuroimaging showed significantly lower αSyn concentrations ( p < 0.02). In the setting AD versus controls, the area under the receiver operating characteristic (ROC) curve was 0.804 [0.712; 0.896] with the sensitivity and the specificity of 0.863 and 0.618, respectively. αSyn in AD patients does not differentiate between subjects with- and without EP. Its increased average concentration reflects probably neurodegenerative process, and is not specific for any pathophysiologic mechanisms. Further studies are necessary to explain the role of CSF αSyn as a potential biomarker.